Two new species of the genus Metapocyrtus Heller, 1912 from the islands of Homonhon and Mindanao, Philippines, with taxonomic notes (Coleoptera: Curculionidae, Entiminae, Pachyrynchini) - Cabras, Analyn A.; Mainda, Tobias (Zootaxa, 2023)
Two new species of the genus Metapocyrtus Heller, 1912 from the islands of Homonhon and Mindanao: Metapocyrtus (Sclerocyrtus) rolandmuelleri Cabras and Mainda sp. nov. and Metapocyrtus (Sclerocyrtus) dabaw Cabras and Mainda sp. nov. are described and illustrated in this paper. It is also proposed to transfer a species from the subgenus Artapocyrtus Heller, 1912 to Sclerocyrtus Heller, 1912: Metapocyrtus (Sclerocyrtus) latinasus Heller, 1925.